2015
DOI: 10.1002/ccd.26108
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of catheter‐directed thrombolysis in pulmonary embolism and outcome difference between systemic thrombolysis and catheter‐directed thrombolysis

Abstract: Objective: The aim of the study was to assess the utilization of catheter-directed thrombolysis (CDT) and its comparative effectiveness against systemic thrombolysis in acute pulmonary embolism (PE). Background: Contemporary real world data regarding utilization and outcomes comparing systemic thrombolysis with CDT for PE is sparse. Methods: We queried the Nationwide Inpatient Sample from 2010 to 2012 using the ICD-9-CM diagnosis code 415.11, 415.13, and 415.19 for acute PE. We used propensity score analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 25 publications
(23 reference statements)
2
75
0
Order By: Relevance
“…A recent study by Patel and colleagues 15 using NIS data found that CDI provided a significant benefit for in-hospital mortality compared to ST, with nearly a 40% relative risk reduction and significant decrease in odds (CDI: 13.36%; ST: 21.81%; OR 0.55, 95% CI [0.36–0.85]; P=.007). Our methodology differed from theirs in terms of patient selection, resulting in a larger amount of patients in our study and reflecting a higher sensitivity of identification of acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Patel and colleagues 15 using NIS data found that CDI provided a significant benefit for in-hospital mortality compared to ST, with nearly a 40% relative risk reduction and significant decrease in odds (CDI: 13.36%; ST: 21.81%; OR 0.55, 95% CI [0.36–0.85]; P=.007). Our methodology differed from theirs in terms of patient selection, resulting in a larger amount of patients in our study and reflecting a higher sensitivity of identification of acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that LOS following PE ranges from 5 to 11 days. [13][14][15][16][17] If a PERT participates in the care of a patient for the duration of the hospitalization (which was not true for the WCMC PERT), then it can give discharge recommendations and potentially impact LOS. However, a PERT may also impact LOS based on how it manages severe PE.…”
Section: Discussionmentioning
confidence: 99%
“…8 The reasons for this decrease may relate to the continued concern regarding devastating bleeding complications, particularly ICH, as well as the results of recent studies suggesting relative safety and efficacy of CBT. 5 Unfortunately, as effective as systemic thrombolysis can be, the incidence of major bleeding and ICH is clearly higher than with anticoagulation alone. 9,10 This persisting obstacle together with advances in surgical techniques and catheter technology has prompted alternate treatment options, including lower dose systemic fibrinolysis, surgical embolectomy, and a number of catheter-based approaches.…”
Section: Definitions: Severity Of Acute Pulmonary Embolism-therapeutimentioning
confidence: 99%
“…A recent analysis of the National Inpatient Sample database indicates that utilization of CBT has increased since 2010. 5 It was shown, based on a propensity-matched analysis of a cohort of 352 inpatients with PE who underwent CBT compared with 352 inpatients who had systemic thromboly-sis, that the inhospital mortality rate was approximately 10% which was significantly lower than the rates for systemic thrombolysis ($20%). There were very low rates of intracranial hemorrhage (ICH) (0.28%) and no ICH after 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation